Role of actin-binding proteins in prostate cancer - Fu, Fangzhi; Yu, Yunfeng; Zou, Bo; Long, Yan; Wu, Litong; Yin, Jubo; Zhou, Qing (Frontiers in Cell and Developmental Biology, 2024)
The molecular mechanisms driving the onset and metastasis of prostate cancer remain poorly understood. Actin, under the control of actin-binding proteins (ABPs), plays a crucial role in shaping the cellular cytoskeleton, which in turn supports the morphological alterations in normal cells, as well as the invasive spread of tumor cells. Previous research indicates that ABPs of various types serve distinct functions, and any disruptions in their activities could predispose individuals to prostate cancer. These ABPs are intricately implicated in the initiation and advancement of prostate cancer through a complex array of intracellular processes, such as severing, linking, nucleating, inducing branching, assembling, facilitating actin filament elongation, terminating elongation, and promoting actin molecule aggregation. As such, this review synthesizes existing literature on several ABPs linked to prostate cancer, including cofilin, filamin A, and fascin, with the aim of shedding light on the molecular mechanisms through which ABPs influence prostate cancer development and identifying potential therapeutic targets. Ultimately, this comprehensive examination seeks to contribute to the understanding and management of prostate diseases.